2008
DOI: 10.1111/j.1600-0609.2008.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab therapy in adult patients with relapsed or refractory immune thrombocytopenic purpura: long‐term follow‐up results

Abstract: Objective:  To evaluate the long‐term activity and toxicity profile of rituximab in adult patients with idiopathic immune thrombocytopenic purpura (ITP). Patients and methods:  Twenty‐six patients with active and symptomatic ITP relapsed or refractory received weekly infusions of rituximab 375 mg/m2 for 4 wk. Median time from diagnosis to rituximab was 34.5 months. The following parameters of efficacy and toxicity were considered: complete response (CR) and partial response (PR), relapse rate, relapse‐free sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 12 publications
5
73
0
3
Order By: Relevance
“…The results of our analysis confirm the short to mid-term effect of rituximab salvage therapy in adult patients with ITP reported earlier by our group and other authors [4][5][6][7][8][9][10][11][12]. Our data might suggest SD is the preferable therapeutic regimen due to the shorter timing of response, the higher response rate, the lower incidence of relapse, and the similar safety profile.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of our analysis confirm the short to mid-term effect of rituximab salvage therapy in adult patients with ITP reported earlier by our group and other authors [4][5][6][7][8][9][10][11][12]. Our data might suggest SD is the preferable therapeutic regimen due to the shorter timing of response, the higher response rate, the lower incidence of relapse, and the similar safety profile.…”
Section: Discussionsupporting
confidence: 90%
“…Fifty-seven consecutive Caucasian adult patients were included into this survey; the results observed in the first 27 patients have already been reported [12] but had been in this article updated with longer follow-up. Table I summarizes patients' main characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceccarelli's safety study on SLE found adverse event rates comparable to the placebo, with the only differences being leukopenia (12.3% vs. 4.2%), neutropenia (5.5% vs. 1.4%) and hypotension (11% vs. 4.2%). 15 Medeot et al, 16 on the other hand, ascertained a rituximab safety profile in patients with refractory ITP. They found that rituximab administration was associated with two episodes of short-term toxicity, namely a mild infusion reaction and a case of serum sickness syndrome, which improved rapidly with steroids; no infectious or other significant longterm complications were documented.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CD-20 antigen (monoclonal antibodies against B-cell) was analyzed in systematic metaanalysis which included more than 300 ITP patients [20][21][22][23]. The response rate was 25-75%, CR -33% of cases, lasting up to three years [22][23][24][25] and the only common sideeffect was infusion reactions [26]. Patel V. and colleagues documented ITP patients treated with monoclonal antibodies 5-year relapse-free and treatment-free survival of 72% and 61% respectively [27].…”
Section: Discussionmentioning
confidence: 99%